Chapter review of "Fundamental techniques in handling people" from Dale Carnegie's "How to win friends and influence people" - Silma, Nazula; Yudistira, Cokorda Gede Putra; Kasiani, Kasiani; Waelan, Waelan; Abdurrahim, Abdurrahim; Sari, Rahma B (Journal of Education, Social & Communication Studies, 2024)
This study aims to examine Dale Carnegie's "Fundamental Techniques in Handling People," the first chapter of his seminal work "How to Win Friends and Influence People", Through document analysis, we will closely read the chapter, identifying key arguments, practical strategies, and underlying assumptions about human behaviour. We also review relevant secondary literature that provides context and critical analysis of Carnegie's work. We explore Carnegie's three core principles: avoiding criticism, expressing genuine appreciation, and arousing a "deep yearning desire" in others. We analyse the effectiveness of each principle, explore potential limitations, and consider cultural or historical specificities that might influence their application. Conclusion: We synthesize our analysis to evaluate the overall effectiveness of Carnegie's techniques in building positive relationships and achieving personal goals. We also consider the enduring relevance of his advice in the contemporary world. Pedagogical Impact: Finally, we explore the chapter's potential application in educational settings. We consider how its principles can be adapted to enhance interpersonal communication, conflict resolution, and leadership skills in students.